2002
DOI: 10.1093/ps/81.7.1065
|View full text |Cite
|
Sign up to set email alerts
|

The ontogeny of fatty acid-binding protein in turkey (Meleagridis gallopavo) intestine and yolk sac membrane during embryonic and early posthatch development

Abstract: Experiments were conducted to confirm the existence and ontogeny of fatty acid binding protein (FABP) in the intestine and yolk sac membrane of turkey poults (Meleagridis gallopavo) during embryonic and early posthatch development. Intestinal (I-) FABP was measured using an immunoblot procedure incorporating anti-chick liver (L-)FABP antisera. FABP activity in both tissues was also confirmed with a ligand-binding assay incorporating 14C-oleic acid. I-FABP did not cross-react with chick L-FABP antisera until ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Similar changes were also reported in cytosolic fatty acid binding protein (FABP) in chick and turkey, which showed significant increases after hatch (Katongole and March, 1980). Ding and Lilburn (2002) have suggested that intestine in bird is still an immature organ at hatch and the expression of fatty acid transporters could be representatives of many physiological processes that need posthatch development before digestive functions become mature. In addition, the increase in FAT/CD36 expression may be in concert with the uptake of dietary fat.…”
Section: Discussionsupporting
confidence: 61%
“…Similar changes were also reported in cytosolic fatty acid binding protein (FABP) in chick and turkey, which showed significant increases after hatch (Katongole and March, 1980). Ding and Lilburn (2002) have suggested that intestine in bird is still an immature organ at hatch and the expression of fatty acid transporters could be representatives of many physiological processes that need posthatch development before digestive functions become mature. In addition, the increase in FAT/CD36 expression may be in concert with the uptake of dietary fat.…”
Section: Discussionsupporting
confidence: 61%
“…The serum triglyceride concentration, peaking at the first sampling (3 days of age), indicates a typically intensive early lipid metabolism and transport (Noble and Cocchi, 1990), being especially characteristic of precocial species (Vleck and Vleck, 1987). The later, general decrease of serum triglyceride concentration seems to be in strong agreement with the results of Ding and Lilburn (2002), describing the decline of the specific activity of intestinal fatty acid binding protein (FABP) in the early posthatch period in turkeys. Moreover, in this early interval one of the main energy sources is the lipid content of the yolk, while during the fattening period this is the feed.…”
Section: Serum Metabolitessupporting
confidence: 53%
“…Changes in the expression of the intestinal solute carrier (SLC) gene family in the small intestine during late embryonic and early post-hatch development have been reported with marked increases in expression of the amino acid transporters rBAT, y(+) LAT-2 and EAAT3, the peptide transporter PepT1 and the sugar transporters SGLT1, GLUT2 and GLUT5 . Fatty acid binding protein levels are first detected at hatch in turkeys and increase during early post-hatch growth (Ding and Lilburn, 2002).…”
Section: Small Intestinementioning
confidence: 99%